Business Innovation in Indonesia: A Systematic Review - Uula, Mimma Maripatul (Business and Sustainability, 2022)
This study aims to see the development of research on the topic of "Business Innovation in Indonesia" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Business Innovation in Indonesia" which comes from the Scopus database with a total of 535 artike documents l journal. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of research development "Business Innovation in Indonesia" in Indonesia. The results of the study found that based on bibliometric keyword mapping, there are 6 clusters that can become research paths with topics related to Empowering Creative Economies and Business Innovation in Indonesia, Sustainable Firm Performance and Business Innovation in Indonesia, Enhancing Competitive Advantage and Business Innovation in Indonesia, Optimizing Business Performance and Business Innovation in Indonesia, Digital Transformation and Business Innovation in Indonesia and Covid-19 and Business Innovation in Indonesia. Furthermore, the most used words are competitive advantage, creativity, business performance, capability, technology, entrepreneur, covid, and sustainability.